Access to functionalized pyrrolidones via copper-catalyzed aminooxygenation of unactivated alkenes. Issue 9 (27th February 2020) - Rao, Wei-Hao; Jiang, Li-Li; Chen, Fang-Yuan; Zhang, Meng; Guo, Yi-Yuan; Chen, Jia-Jia; Cui, Ying; Zou, Guo-Dong; Tang, Lin
Graphical abstract: Highlights: Low-cost copper catalysis. Selective exo - N -cyclization. Further derivatizations. Abstract: A simple and efficient copper-catalyzed aminooxygenation of unactivated alkenes with commercially available (2, 2, 6, 6-tetramethylpiperidin-1-yl)-oxyl (TEMPO) as an oxygen source is reported. With this protocol, a variety of functionalized pyrrolidones were obtained in good to excellent yields, and good tolerance of functional groups and broad substrate scope were observed. Notably, the N -cyclization step selectively proceeded in an exo manner, and this protocol provides an efficient and straightforward approach to prepare vicinal amino alcohols.